Control interno a los inventarios y su incidencia en la rentabilidad de la empresa ferretería promainco, cantón Quevedo, período 2012. Quevedo - Allan Acosta, Betty Aracelly (2015)
This research project aims to make anINTERNAL CONTROL TO THE INVENTORY OF GOODS AND THEIR EFFECT ON THE PROFITABILITY OF THE ENTERPRISE HARDWARE PROMAINCO, Quevedo Canton, 2012. PERIOD "and for this we had to select a commercial company dedicated to Sale of construction materials, iron, rolled, Cement, Nets, Hardware as a provider of these building materials, consequently the objectives are to assess the level of reliability of inventory accounting system to measure the degree of confidence that presents the method applied to the valuation of inventories, to analyze the treatment that the company gives the storage of goods and verify that the safety systems protect and guard the goods of this project. PROMAINCO trading company, is owned by Eduardo Manager Allan Bridge. The percentages obtained in the evaluation of internal control questionnaire to the manager and employees of the company are as follows: it was found that there is a confidence level of 90.10%high, and the risk level of 9.90% Medium Low affecting sales and profitability Company in turn shows an inherent risk of 20% the same impact on the activities of the company. Culminating in this research project with their findings and recommendations scheduled, they provide precisely that inventories of goods providing adequate profitability PROMAINCO.